Determinan Faktor Fundamental Terhadap Return Saham (Studi pada Perusahaan yang Masuk ILQ 45 di Bursa Efek Indonesia) - Widjanarko, Hendro (Jurnal Manajemen Bisnis, 2011)
This reaseach analyzes, (1) fundamental factor influences Price Earning Ratio, Debt to Equity Ratio, Return on Equity, and Book Value simultanteously and partially to return stock on corporate incoming Index liquid 45 (ILQ 45) at Indonesian Stock Exchange (BEI), (2) to identify variable which that influential dominant to return stock on corporate incoming ILQ 45 at IndonesianStock Exchange (BEI). In this reasech, specialed sample as much 17 incoming firms in ILQ to periode 2004-2008 one accomplishes criterions as sample. Findingon observational it, fundamental factors Price Earning Ratio, Debt to Equity ratio, Return on Equity, and Book Value declare for that simultant avaliable influence that significant to return stock, in t test (partial) fundamental factor Price Earning Ratio and Return on Equity partially have significant influence to return stock, and variable Price Earning Ratio (PER) having for dominant to return stoct on corporate incoming deep ILQ 45 of Indonesian Stock Exchange (BEI).